Union of South Africa. Debates of the House of Assembly. Fourth Session Fourth Parliament 1924 - South Africa Parliament (Cape Town Government Printer, 1924)
Debates of the House of Assembly of the Union of South Africa as reported in the Cape Times. Debates of the House of Assembly Union of South Africa Debatten van de Volksraad / Unie van Zuid-Afrika. South Africa Politics and government.
Fourth Session, 4th Parliament, vol. 1 (25 Jan.-10 Apr. 1924)-4th Session, 12th Parliament, v. 108 (1 May-26 May 1961). Vol. 1 of this series published parallel with the Dutch title: Debatten van de Volksraad.
Keywords: Union of South Africa; Debates; JC044662; 25 January to 10 April; 1924; Fourth Session - Fourth Parliament; vol 1; Hansard